Catheter ablation versus medical rate control for persistent atrial fibrillation in patients with heart failure: A PRISMA-compliant systematic review and meta-analysis of randomized controlled trials. Issue 30 (July 2016) - Zhu, Min; Zhou, Xinbin; Cai, Hongwen; Wang, Zhijun; Xu, Huimin; Chen, Shenjie; Chen, Jie; Xu, Xiaoming; Xu, Haibin; Mao, Wei
Abstract: Background: The effectiveness of restoring the sinus rhythm by catheter ablation relative to that of medical rate control for persistent atrial fibrillation (AF) patients with heart failure (HF) remains to be defined. Methods: We systematically searched Embase, Pubmed, the Cochrane Library, and ClinicalTrials.gov for articles that compared the outcomes of interest between catheter ablation and medical rate control therapy in persistent AF patients with HF and left ventricular systolic dysfunction (LVSD). The primary endpoint was the change in the left ventricular ejection fraction (LVEF) following catheter ablation or medical rate control therapy relative to baseline. Other endpoints included changes in cardiac function and exercise capacity, including the New York Heart Association (NYHA) class, the brain natriuretic peptide (BNP) level, the peak oxygen consumption (peak VO2 ), the 6-minute walk test (6MWT) results, and quality of life (QOL). Results: Three randomized controlled trials (RCTs) with 143 patients were included. At the overall term follow-up, catheter ablation significantly improved the LVEF (mean difference [MD]: 6.22%; 95% confidence interval [CI]: 0.7–11.74, P = 0.03) and peak VO2 (MD: 2.81 mL/kg/min; 95% CI: 0.78–4.85, P = 0.007) and reduced the NYHA class (MD: 0.9; 95% CI: 0.59–1.21, P < 0.001) and the Minnesota Living with Heart Failure Questionnaires (MLHFQ) scores (MD: −11.05; 95% CI: −19.45 — −2.66, P = 0.01) compared with the medical rate control for persistent AF patients with HF. Alterations in parameters, such as the BNP level, 6MWT, and Short Form-36 (SF-36) questionnaire scores also revealed trends that favored catheter ablation therapy, although these differences were not significant. Conclusion: Catheter ablation resulted in improved LVEF, cardiac function, exercise capacity, and QOL for persistent AF patients with HF compared with the medical rate control strategy.